Decision Support System for Selecting Village Fund BLT Recipients using ROC and WASPAS Methods - Manurung, Marisah Elfrida; Desnelita, Yenny; Hajjah, Alyauma; Duha, Yermias (Sistemasi: Jurnal Sistem Informasi, 2025)
The Village Fund Direct Cash Assistance (BLT) Program is a government initiative aimed at improving social welfare, reducing inequality, and supporting economically disadvantaged communities. However, in practice, the process of determining BLT recipients often faces issues of subjectivity and lack of transparency. This study aims to develop a Decision Support System (DSS) to assist village authorities in selecting BLT recipients objectively and accurately by utilizing the Rank Order Centroid (ROC) and Weighted Aggregated Sum Product Assessment (WASPAS) methods. The ROC method is used to assign weights to each criterion based on their level of importance, while the WASPAS method is applied to rank the recipient candidates according to the established weights. The DSS is developed as a web-based application to ensure easy access for village administrators. System testing results indicate that the ROC method consistently generates weights that reflect the prioritization of criteria, while the WASPAS method proves effective in producing final rankings of potential recipients. As a result, village leaders can make more objective and targeted decisions in determining BLT beneficiaries.